Cytotoxicity of natural and synthetic cannabinoids and their synergistic antiproliferative effects with cisplatin in human ovarian cancer cells - Chen, Ying; Li, Huifang; Liu, Jia; Ni, Jie; Deng, Qicheng; He, Haotian; Wu, Panpan; Wan, Yinsheng; Seeram, Navindra P.; Liu, Chang; Ma, Hang; Zhu, Weipei (Frontiers in Pharmacology, 2024)
Cannabinoids are reported to suppress the growth of ovarian cancer cells, but it is unclear whether structural modifications can improve their cytotoxic effects. Herein, an investigation into the antiproliferative effects of cannabinoids on human ovarian cancer Caov-3 cells identified cannabidiol (CBD) as the most promising compound. Furthermore, chemical modifications of CBD yielded a group of derivatives with enhanced cytotoxicity in Caov-3 cells. Two CBD piperazinyl derivatives (19 and 21) showed augmented antiproliferative effects with an IC50 of 5.5 and 4.1 µM, respectively, compared to CBD's IC50 of 22.9 µM. Further studies suggest that modulation of apoptosis and ferroptosis may contribute to the cytotoxic effects of CBD and its derivatives. In addition, CBD and its derivatives (19 and 21) were explored for their potential synergistic antiproliferative effects in combination with chemotherapeutic agent cisplatin. Compounds 19 or 21 (at 5 µM) combined with cisplatin (1 µM) showed synergistic effect with a combination index of 0.23 and 0.72, respectively. This effect was supported by elevated levels of reactive oxygen species in Caov-3 cells treated with cisplatin combined with 19 or 21. Findings from this study suggest that CBD derivatives with enhanced antiproliferative effects may exert synergistic effects with chemotherapeutic drugs, providing insight into the development of cannabinoid-based adjuvant agents for the management of ovarian cancer.